2007
DOI: 10.1002/chem.200600748
|View full text |Cite
|
Sign up to set email alerts
|

Protonated Heme

Abstract: The ions formally corresponding to protonated heme [Fe(II)-hemeH](+) have been obtained by collision-induced dissociation from the electrospray ionization of microperoxidase (MP11) and their gas-phase chemistry has been studied by FTICR mass spectrometry. H/D-exchange reactions, used as a tool to gain information on the protonation sites in polyfunctional molecules, show that labile hydrogens pertain to the propionyl substituents at the periphery of the protoporphyrin IX. Several conceivable isomers for proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 88 publications
6
52
0
Order By: Relevance
“…10 The so-obtained description of [Fe II -hemeH(NO)] + is consistent with that of an iron(II)-heme bound to NO. A binding energy of 140 kJ mol -1 is calculated with respect to dissociation into triplet [Fe II -hemeH] + and 2 NO.…”
Section: Binding Energies Of the [Fe III -Heme(no)] + And [Fe Ii -Hemsupporting
confidence: 65%
See 2 more Smart Citations
“…10 The so-obtained description of [Fe II -hemeH(NO)] + is consistent with that of an iron(II)-heme bound to NO. A binding energy of 140 kJ mol -1 is calculated with respect to dissociation into triplet [Fe II -hemeH] + and 2 NO.…”
Section: Binding Energies Of the [Fe III -Heme(no)] + And [Fe Ii -Hemsupporting
confidence: 65%
“…When [Fe II -hemeH] + ions extracted from the ESI source and isolated in the FT-ICR cell are exposed to a stationary concentration of selected neutral ligands (L), an addition reaction may be observed, leading to [Fe II -hemeH(L)] + . For the addition reaction between [Fe II -hemeH] + and ligands such as NO and (C 2 H 5 O) 3 P the second order rate constants of 0.33 × 10 -10 cm 3 molecule -1 s -1 and 4.0 × 10 -10 cm 3 molecule -1 s -1 , respectively, have been reported, as determined at 300 K. 10 In the present, thorough study, a vast array of compounds were tested and many were found unreactive, including biologically active diatomics (O 2 and CO), nitrogen bases (NH 3 , CH 3 NH 2 , CH 3 CN), carboxylic acids and derivatives (acetic acid, CH 3 C(O)N(CH 3 ) 2 ), alcohols and ethers (CH 3 OH, tetrahydrofuran, 2-methoxypropene), ketones ((CH 3 ) 2 CO), and sulfides ((CH 3 ) 2 S, (CH 3 ) 2 S 2 )). In relatively few cases, adduct ions are formed and the relevant thermodynamic features of the process are now reported.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This novel complex has been thoroughly characterized both by its gas phase reactivity and by computations searching for plausible structures. 23 By DFT calculations, the relative stability of various isomers holding the additional proton on different sites of the porphyrin ligand, on its substituents and on the metal atom itself has been assessed. The most stable isomer is the one corresponding to protonation on one of the peripheral vinyl groups and the optimized structure is shown in Figure 1.…”
Section: Formation Of Charged Iron(ii)-and Iron(iii)-heme Ions In Thementioning
confidence: 99%
“…In the study of association reactions either the reactant ion or the formed ion-neutral complex may be isolated and their reaction kinetics evaluated at varying neutral pressure. In this way the rate constants for the forward and reverse reaction (k f and k r , respectively) may be evaluated ( 23,25 Their ratio, yielding the reaction equilibrium constant, has been compared with the equilibrium constant value derived from the steady ion abundance ratio observed at long reaction time, the two values nicely matching each other. Exemplary kinetic plots are shown in Figure 2 .…”
Section: Kinetic and Thermodynamic Parameters For No Binding To Iron(mentioning
confidence: 99%